2019
DOI: 10.1155/2019/1612456
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Properties of Calcium Titanate, Strontium Titanate, and Strontium Calcium Titanate Powders Synthesized by Solution Combustion Technique

Abstract: Calcium titanate (CaTiO3), strontium titanate (SrTiO3), and strontium calcium titanate (SrxCa1−xTiO3) are widely recognized and utilized as dielectric materials. Their electrocatalytic properties, however, have not been extensively examined. The aim of this research is to explore the electrocatalytic performance of calcium titanate, strontium titanate, and strontium calcium titanate, as potential sensing materials. Experimental results revealed that CaTiO3, SrTiO3, and Sr0.5Ca0.5TiO3 powders synthesized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…On the other hand, the E g values for CaTiO 3 and MgTiO 3 were observed to be 3.0 eV and 3.12 eV, respectively which are slightly higher than those of their oxides. The E g value for CaTiO 3 was reported to be in the range of 3.0–3.6 eV versus SHE, while the E g value for MgTiO 3 was in the range of 3.0–3.2 eV versus SHE 21 , 36 , 39 , 43 .
Figure 4 Tauc’s Plots for bandgap estimation of ( a ) CaO, ( b ) CaTiO 3 , ( c ) MgO and ( d ) MgTiO 3 .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the E g values for CaTiO 3 and MgTiO 3 were observed to be 3.0 eV and 3.12 eV, respectively which are slightly higher than those of their oxides. The E g value for CaTiO 3 was reported to be in the range of 3.0–3.6 eV versus SHE, while the E g value for MgTiO 3 was in the range of 3.0–3.2 eV versus SHE 21 , 36 , 39 , 43 .
Figure 4 Tauc’s Plots for bandgap estimation of ( a ) CaO, ( b ) CaTiO 3 , ( c ) MgO and ( d ) MgTiO 3 .
…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peaks at 1477 and 874 cm −1 are attributed to the C–O asymmetrical and symmetrical vibrations. The bands that appeared at 459 cm −1 are due to the existence of Ca–O metal oxide which was transformed from CaCO 3 in the eggshells 36 , 37 . In the case of CaTiO 3 , the broad peaks at around 3311 and 1419 cm −1 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specific surface area of 8.69 m 2 g −1 was observed. Assuming that the particles are spherical, nonporous and also the theoretical density of the individual materials, the relationship between particle size and specific surface area was expressed by the following equation (5) [13]:…”
Section: Microstructure and Specific Surface Areamentioning
confidence: 99%
“…Nanoparticulate doped-metal oxides emerge as promising sensor candidates. This is attributed to substantial reactive sites on surface and enhanced electron transfer [8][9][10][11]. According to Yu et al, high electronic conductivity was observed in nanoparticulate Zndoped TiO2 [12].…”
Section: Introductionmentioning
confidence: 97%